THE EFECT OF USE FISH OIL ON FEED TO COMMERCIAL PIECES OF BROILER CARCASS - I P. B., Sukerta; Nuriyasa, I M.; Astawa, I P. A. (Jurnal Peternakan Tropika; Vol 8 No 3 (2020): Vol. 8 No. 3 Tahun 2020; September - December, 2020)
This study aims to determine the effect of fish oil on commercial cutouts of carcass. This research was conducted in Dajan Peken Village, Tabanan for 6 weeks. The research design used was a completely randomized design (CRD) consisting of 3 treatments and 7 replications so that there were 21 experimental units. The 3 treatments were P0 rations without fish oil (0%) in feed, P1 rations with 3% fish oil in feed, and P2 rations with 6% fish oil in feed. Each experimental unit used 2 broilers (unsex) with a weight range of 440 ± 30 g. The variables observed were carcass proportion and commercial cuttings including chest, wings, upper thighs, lower thighs and back. The results showed that the proportion of carcass and commercial pieces tended not to be adhered to by the addition of 3% and 6% fish oil in the feed compared to the control, the analysis of variance showed that the treatment was not significantly different (P> 0.05). Based on this study it can be neglected that the use of fish oil at a dose of 6% in the feed did not increase the proportion of carcass and carcass pieces of broiler chickens including breast, wings, upper thighs, and lower thighs.   Key words : Broiler, Fish oil, Broiler carcass, commercial pieces